Case reportArtificial dermatitis – a case study - Rosińska, Anna; Walkowiak, Hanna; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Psychodermatologic disorders are conditions involving an interaction between the skin and the mind. Understanding the psychosocial and occupational context of skin diseases is critical for the optimal management of psychodermatological disorders. Dermatitis artefacta (factitial dermatitis) refers to conditions in which the patient self-inflicts excoriations with his own nails, sharp instruments, burning cigarettes or chemicals. There are instances in which recognition of this disorder is difficult. Histological findings are not characteristic and diagnosis depends on the clinical presentation. The differential diagnosis of cutaneous lesions is extensive, depending on the lesion type. In this article, the authors describe a 51-year-old patient with bizarre-shaped lesions, which consist of linear or geometric outlines located on the right leg. Diagnosis of dermatitis arteficialis was based on clinical grounds, including bizarre-looking lesions, sites accessible to the patients and absence of other dermatologic diseases to explain the dermatosis.